De novo Transcriptome Assembly and Comparative Analysis Highlight the Primary Mechanism Regulating the Response to Selenium Stimuli in Oats (Avena sativa L.) - Liu, Tao; Liu, Xiaoting; Zhou, Rangrang; Chen, Hong; Zhang, Huaigang; Zhang, Bo (Frontiers in Plant Science, 2021)
Selenium is an essential microelement for humans and animals. The specific processing technique of oats can maximize the preservation of its nutrients. In this study, to understand the genetic response of oats in a high-selenium environment, oats were treated with sodium selenate for 24 h, and transcriptome analysis was performed. A total of 211,485,930 clean reads composing 31.30 Gb of clean data were retained for four samples. After assembly, 186,035 unigenes with an average length of 727 bp were generated, and the N50 length was 1,149 bp. Compared with that in the control group, the expression of 7,226 unigenes in the treatment group was upregulated, and 2,618 unigenes were downregulated. Based on the sulfur assimilation pathway and selenocompound metabolic pathway, a total of 27 unigenes related to selenate metabolism were identified. Among them, the expression of both key genes APS (ATP sulfurylase) and APR (adenosine 5′-phosphosulfate reductase) was upregulated more than 1,000-fold under selenate treatment, while that of CBL (cystathionine-β-synthase) was upregulated 3.12-fold. Based on the transcriptome analysis, we suspect that the high-affinity sulfur transporter Sultr1;2 plays a key role in selenate uptake in oats. A preliminary regulatory mechanism explains the oat response to selenate treatment was ultimately proposed based on the transcriptome analysis and previous research.